(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
Are adventure/wilderness type therapies limited to geography? Can they only take place in what are traditionally considered ’wild spaces’ or is it possible to facilitate a sense of adventure and wilderness in urbanised areas? This article explores the idea of micro-adventure/wilderness therapies for children and young people both for group work and one-to-one support, and demonstrates how to deliver adventure type interventions in highly developed areas.